Ectopic miRNA network and the crosstalk between different signalling pathways during epithelial–mesenchymal transition and mesenchymal–epithelial transition - Razak, Eliza; Yusof, Faridah; Ahmad Raus, Raha (Kulliyyah of Engineering, International Islamic University Malaysia, 2016)
The tumor microenvironment (TEM) comprise of various cellular and molecular components such as fibroblasts, immune cells, bone marrow-derived inflammatory cells, endothelial cells, extracellular matrix (ECM), and signaling molecules. The complex crosstalk between TEM components and signaling pathways can give rise to tumorigenesis, progression, and angiogenesis as well as micro-metastasis and macro-metastasis. MicroRNAs (miRNAs) are small, non-coding extracellular RNAs involved in post-transcriptional regulation of gene silencing or degradation by base paring at open reading frame (ORF) region of the target mRNA. Recent advances in the miRNA field have driven to the understanding of multiple regulatory aspects concerning cancer biology. Acquisition of aberrant miRNA expression level in neoplastic tumor compared with normal tissue are promising biomarkers for cancer diagnosis. Epithelial-mesenchymal transition (EMT) is a reversible process in which neoplastic epithelial cells expressed mesenchymal phenotypes and resulting in alteration of cell autonomous mechanisms. EMT enables epithelial cells to lose their cell polarity, acquire cancer stem cell-like properties which favor tumor invasion, extravasation and metastasis. Mesenchymal–epithelial transition (MET) is the inverse process of EMT. This results in stabilization of distant metastases by permitting cancerous cells to recoup epithelial phenotypes and integrate into distant organs. Ectopic microRNA expression and disturbed signaling pathways have been associated with orchestrating EMT and MET processes. However, the exact molecular mechanisms behind oncogenic EMT and MET have remained widely elusive. This review describes the co-regulatory loops among miRNAs, target genes and important regulatory pathways involved in oncogenic EMT and MET.